Cultivating staff equality, diversity, and inclusion in higher education in the post-pandemic era: an organizational compassion perspective - Hashemi Toroghi, Haleh; Denney, Fiona; Simpson, Ace Volkmann (Frontiers in Sociology, 2024)
The COVID-19 pandemic has exacerbated pre-existing challenges faced by academic staff in UK higher education and drawn attention to issues of Equality, Diversity, and Inclusion (EDI). Amidst global competitiveness and workplace pressures, challenges such as managerialism, increased workload, and inequalities have worsened, significantly impacting mental health. This paper presents a conceptual analysis connecting EDI with organizational compassion within the context of Higher Education. The prioritization of organizational compassion is presented as a means to enhance sensitivity to EDI in the reconstruction of post-pandemic learning environments. Anchored in the organizational compassion theory and the NEAR Mechanisms Model, our study contributes to the intersection of the organizational compassion, EDI and higher education literatures by exploring how fostering compassion relations can contribute to enhancing EDI. This offers a new perspective to creating a more humane and supportive higher education environment.